Improving educational productivity - Monk, David H.; Walberg, Herbert J., 1937-; Wang, Margaret C. (Emerald Publishing Limited : Information Age Pub., 2001)
Covering such issues as teaching quality, the interface between public and private schooling, and measuring school efficiency, this text addresses the improvement of educational productivity in the USA.
Edited conference papers.
Keywords: Educational productivity -- United States -- Congresses.; Education -- Economic aspects -- United States -- Congresses.; Education -- United States -- Finance -- Congresses.; elektronické knihy; Conference papers and proceedings.; Education -- Administration -- General.; Educational administration and organization.; electronic books